Evaluation of Lycopus uniflorus water extract for anti-inflammatory, anti-ulcerogenic and antioxidant activities - Saade, S. (2009)
Lycopus uniflorus, commonly known as bugleweed, is usually found near freshwater wetland and has a wide abundance in Lebanon. The plant has some folk use for treatment of gastrointestinal disorders and reduction of inflammation. No studies were conducted on Lycopus uniflorus, but other species were reported to possess anti-allergic [1], anti-inflammatory [2], antihyperthyroidism [3], Yarnell and Abascal, 2006 E. Yarnell and K. Abascal, Botanical medicine for thyroid regulation, Alternative and Complementary Therapies (2006), pp. 107–112. Full Text via CrossRef | View Record in Scopus | Cited By in Scopus (2) antioxidant [4] and anticancer [5] activities. The present study was conducted to investigate the potential role of L. uniflorus water extract on inflammation and gastric ulcer in rat model. Pretreatment with the extract (50, 100 and 200mg/kg BW by gastric gavage) produced a dose dependent protection against gastric ulcer induced by 60% ethanol. Results showed that 50mg/kg and 100mg/kg caused 20.87 and 80.10%, respectively, compared to 41.70% for cimetidine at 11.5mg/kg BW dose. The same doses were used to test for anti-inflammatory activity against edema induced in hind paw by carrageenan. Intra-peritoneal doses of 100 and 200mg/kg BW of the extract showed significant (p <0.05) anti-inflammatory activity when compared with the untreated control. The highest inhibition of edema development was achieved at 100mg/kg BW dose and the edema was decreased by 67% compared with diclofenac (60%) at 10mg/kg BW. No signs of toxicity were observed at used doses. Antioxidant activity was established using DPPH assay and the extract exhibited high DPPH radical scavenging activity (80.4%). The estimated total phenolic content was 228.5 GAE per gram. The results show that Lycopus uniflorus possesses a potential anti-inflammatory, anti-ulcerogenic and antioxidant activities.